2021
DOI: 10.1111/aogs.14135
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of pregnancies complicated by late fetal growth restriction undergoing induction of labor with dinoprostone compared with cervical balloon: A retrospective, international study

Abstract: Introduction The aim of this study was to compare vaginal dinoprostone and mechanical methods for induction of labor (IOL) in pregnancies complicated by late fetal growth restriction. Material and methods Multicenter, retrospective, cohort study involving six referral centers in Italy and Spain. Inclusion criteria were pregnancies complicated by late fetal growth restriction as defined by Delphi consensus criteria. The primary outcome was the occurrence of uterine tachysystole; secondary outcomes were either c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
(58 reference statements)
0
10
1
1
Order By: Relevance
“…11 These findings further support the Accepted Manuscript efficacy and safety of prostaglandins in the induction for patients with oligohydramnios 9,11 and fetal growth restriction. 13,14 Conversely, contrary to a recent metanalysis, 13 our study did not demonstrate an increased rate of CD for abnormal fetal heart rate tracing in pregnancies complicated by oligohydramnios with and without FGR. This difference may be because our results are derived from a secondary analysis of a parent database comprised purely of high-risk pregnant women.…”
Section: Results In Context Of What Is Knowncontrasting
confidence: 99%
See 2 more Smart Citations
“…11 These findings further support the Accepted Manuscript efficacy and safety of prostaglandins in the induction for patients with oligohydramnios 9,11 and fetal growth restriction. 13,14 Conversely, contrary to a recent metanalysis, 13 our study did not demonstrate an increased rate of CD for abnormal fetal heart rate tracing in pregnancies complicated by oligohydramnios with and without FGR. This difference may be because our results are derived from a secondary analysis of a parent database comprised purely of high-risk pregnant women.…”
Section: Results In Context Of What Is Knowncontrasting
confidence: 99%
“…Previous studies have revealed contradictory findings in regard to neonatal adverse events in patients with fetal oligohydramnios and those with FGR. Di Mascio et al in 2021 showed a significant increase in the composite of adverse neonatal outcomes with the use of PGE 2 (26.1%) as compared to mechanical methods (16.7%) in patients with FGR (p=0.013) 14 .…”
Section: Results In Context Of What Is Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…В метаанализе, проведенном группой итальянских и германских исследователей и включавшем 1 711 наблю дений индукции родов при ЗРП и маловесном плоде (вла галищная вставка с динопростоном -571, мизопростол -693, баллонный катетер -341), было показано, что часто та кесарева сечения, проведенного в связи с не обнадеживающим статусом плода по данным КТГ, была в 2 раза выше при динопростоне [46]. Сходные результа ты были получены в многоцентровом исследовании, про-веденном в 6 центрах Италии и Испании и включавшем 571 наблюдение с поздней ЗРП [47]. Таким образом, обзор данных литературы свидетельствует об эффектив ности и безопасности влагалищной системы с динопростоном для подготовки шейки матки и родовозбуждения.…”
Section: Introductionunclassified
“…Intravenous oxytocin infusion and amniotomy are recommended when the cervix is favorable, otherwise cervical ripening is necessary to increase the likelihood of successful induction [16]. Several methods of cervical ripening are commonly used because the data currently available do not justify to recommend one method over any other [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%